The choice of method of dispersion the thickener for the production of the recycling plastic grease - Grigorov, Andrey; Tulskaya, Alena; Nahliuk, Mykhailo; Karchakova, Valeriia (My University, 2019)
The results of dispersing the thickener in the area of grease using a paddle stirrer (rotational speed = 100 and 1000 rpm) and ultrasonic treatment with a frequency of 44 kHz have been presented. It has been concluded that ultrasonic dispersion allows us to increase the dispersion of the thickener up to 3-5 microns and spread it evenly in the grease comparing to the mechanical dispersion. Increasing the degree of dispersion of the thickener allows improving the stability of the obtained grease, its adhesive properties. Also it allows reducing the duration of the process of greases producing.
Keywords: grease; thickener; dispersion; viscosity; colloidal stability